Migration trends and implications - Filipski, Mateusz J.; Belton, Ben; van Asselt, Joanna; Hein, Aung; Zu, A Myint; Htoo, Kyan; Win, Myat Thida; Thu, Eaindra Theint Theint; Htun, Khun Moe; Ei, Hnin (International Food Policy Research Institute, 2024)
Following economic and political reforms initiated in 2011, the country’s population has been adapting rapidly to new opportunities and challenges, including through relocation and migration. This chapter describes some of the patterns and dynamics related to these population flows, as well as their consequences for Myanmar’s rural economy. Most of the chapter is based on data collected prior to the triple crises, but recent analyses allow us to give an overview of the migration landscape in the post-2020 era at the end of the chapter (MAPSA 2024c). These analyses confirm that overall migration dynamics have largely persisted.